Evaluation of Hypoglycemic Efficacy of Tangningtongluo Formula, a Traditional Chinese Miao Medicine, in Two Rodent Animal Models - Long Cheng; Xiang-bao Meng; Shan Lu; Ting-ting Wang; Yue Liu; Gui-bo Sun; Xiao-bo Sun (Journal of Diabetes Research)
Traditional Chinese medicines largely lack adequate and scientifically rigorous evidence regarding efficacy and functional mechanisms. The present study was aimed to confirm the hypoglycemic effect of Tangningtongluo (TNTL) formula, a traditional Chinese Miao medicine, in two animal models: high-fat diet and streptozotocin- (STZ-) induced diabetic rats and C57BL/KsJ-db/db diabetic mice. After 4 weeks, TNTL intervention in STZ-induced diabetic rats yielded in significant improvement on the glucose tolerance test. Moreover, the islet histopathology showed that oral TNTL reduced the severity of islet necrosis in pancreases tissue. Compared with diabetic controls, a 12-week TNTL treatment regimen (dosages = 0.9, 1.8, and 3.6 g/kg) in db/db mice significantly decreased fasting glucose and HbA1c. Additionally, oral glucose tolerance in TNTL-treated mice improved significantly, compared with diabetic mice receiving metformin. Finally, tissue histopathology and biochemical index evaluations revealed significant improvement in TNTL-treated mice. Taken together, our results show that TNTL exerted a strong hypoglycemic effect in two diabetic rodent animal models, preserving β-cells in the pancreas islet and reducing the risk of diabetic retinopathy and nephropathy.